The Impact of Public Accountant Competence, Audit Review Quality, and Timeliness of Reporting on Client Loyalty through Audit Trust in Accounting Firms in Jakarta - Aulia, Triana Zuhrotun; Puspitasari, Ria; Maulana, Bonnix Hedy; Nurhayadi, Willy; Sudarmanto, Eko (West Science Interdisciplinary Studies, 2025)
This study examines the influence of public accountant competence, audit review quality, and timeliness of reporting on client loyalty, with audit trust serving as a mediating variable. The research was conducted on public accounting firms operating in Jakarta using a quantitative approach. A total of 250 valid responses were collected through a structured questionnaire and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The findings indicate that public accountant competence, audit review quality, and timeliness of reporting have significant positive effects on audit trust. In turn, audit trust significantly influences client loyalty. Moreover, audit trust partially mediates the relationship between each independent variable and client loyalty, underscoring its critical role in shaping long-term client relationships. The study provides both theoretical contributions and practical implications for public accounting firms in fostering client trust and retention.